2012
DOI: 10.1371/journal.pone.0041660
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of XB130 Is Associated with Both the Prognosis and Chemosensitivity of Gastric Cancer

Abstract: XB130 is a newly characterized adaptor protein that was reported to promote thyroid tumor growth, but its role in the progression of other kinds of cancer such as gastric cancer (GC) remains unknown. Accordingly, we investigated the association between XB130 expression and the prognosis of GC patients. The subjects were 411 patients with GC in stages I to IV. XB130 expression was examined in surgical specimens of GC. Kaplan-Meier analysis and the Cox proportional hazards model were used to assess the prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 19 publications
4
50
0
Order By: Relevance
“…Further, nuclear expression of XB-130 was an independent prognostic factor of postoperative survival. Shi et al [13] has reported that both XB130 mRNA and protein expression were detectable in normal gastric tissues. The reduced XB130 protein expression is a prognostic biomarker for shorter survival and a higher recurrence rate in patients with GC, as well as for the response to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, nuclear expression of XB-130 was an independent prognostic factor of postoperative survival. Shi et al [13] has reported that both XB130 mRNA and protein expression were detectable in normal gastric tissues. The reduced XB130 protein expression is a prognostic biomarker for shorter survival and a higher recurrence rate in patients with GC, as well as for the response to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was carried out using the Dako Envision System (Dako, Carpinteria, CA) and rabbit polyclonal anti-XB130 antibody (1:100; OriGene) following the manufacturer's recommended protocol.The staining intensity and extent scores was according to the previous report [13]. Briefly, the staining intensity was scored as 0 (negative), 1 (weak), 2 (medium), or 3 (strong).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…RNA sequence analysis by Illumina Body Map also shows expression in lymph node, adipocytes, adrenal gland, breast, ovary, prostate, and testis (http://www.genecard.org/) [8]. The expression of XB130 protein has also been confirmed with immunohistochemistry staining in human thyroid [14], submucosal glands of esophagus [15], and stomach [16]. …”
Section: Xb130: a Novel Gene And Proteinmentioning
confidence: 99%
“…Although XB130 has not attracted significant attention until recent years, it has been established that XB130 is a comparatively widely expressed protein. A previous study identified that the mRNA is frequently expressed in human spleen and thyroid, and although it si relatively lower, its expression could also be detected in the kidney, brain, lung, pancreas, liver, colon and stomach (40). Additionally, different approaches using several cell lines showed that XB130 tends to be distributed in the cytoplasm.…”
Section: Xb130: a Newly Studied Adaptor Protein In Cancer Signal Tranmentioning
confidence: 98%
“…However, in contrast to the studies indicating a cancer promotion effect of XB130, Shi et al (40) found evidence suggesting that the XB130 mRNA and protein were constitutively expressed in normal gastric tissue, while relatively lower expressed in gastric cancer (GC) cells (40). The study analyzed survival or recurrence in 411 GC patients and noted that low XB130 expression predicted a lower survival and higher recurrence.…”
Section: Xb130 In Cancermentioning
confidence: 98%